Lysine-Directed Post-translational Modifications of Tau Protein in Alzheimer's Disease and Related Tauopathies - Kontaxi, Christiana; Piccardo, Pedro; Gill, Andrew C. (Frontiers in Molecular Biosciences, 2017)
Tau is a microtubule-associated protein responsible mainly for stabilizing the neuronal microtubule network in the brain. Under normal conditions, tau is highly soluble and adopts an ‘unfolded’ conformation. However, it undergoes conformational changes resulting in a less soluble form with weakened microtubule stabilizing properties. Altered tau forms characteristic pathogenic inclusions in Alzheimer’s disease and related tauopathies. Although tau hyperphosphorylation is widely considered to be the major trigger of tau malfunction, tau undergoes several post-translational modifications at lysine residues including acetylation, methylation, ubiquitylation, SUMOylation and glycation. We are only beginning to define the site-specific impact of each type of lysine modification on tau biology as well as the possible interplay between them, but, like phosphorylation, these modifications are likely to play critical roles in tau’s normal and pathobiology. This review summarizes the latest findings focusing on lysine post-translational modifications that occur at both endogenous tau protein and pathological tau forms in AD and other tauopathies. In addition, it highlights the significance of a site-dependent approach of studying tau post-translational modifications under normal and pathological conditions.